Amanauhyphes saguassu: a new genus and species of Leptohyphidae (Ephemeroptera: Ephemerelloidea) from Northern Brazil - Salles, Federico F. (2006)
Amanahyphes saguassu gen. et sp. n. from the Amazon basin is described and illustrated from all life stages. This is the second known genus in Leptohyphidae to show divided eyes in the male, a rather infrequent characteristic in the family. Some defining characters of this new taxon include: adults dipterous, forewings with Cu-A lobe not enlarged, forceps bisegmented, and nymphs slender with very long legs, abdominal gills on segments II –V, and subquadrate operculate gills on abdominal segment II.gen. et sp. n. from the Amazon basin is described and illustrated from all life stages. This is the second known genus in Leptohyphidae to show divided eyes in the male, a rather infrequent characteristic in the family. Some defining characters of this new taxon include: adults dipterous, forewings with Cu-A lobe not enlarged, forceps bisegmented, and nymphs slender with very long legs, abdominal gills on segments II –V, and subquadrate operculate gills on abdominal segment II.